2022
DOI: 10.5603/fhc.a2022.0013
|View full text |Cite
|
Sign up to set email alerts
|

A chronic moderate methionine administration induced hyperhomocysteinemia associated with cardiovascular disease phenotype in the sand rat Psammomys obesus

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially. www.journals.viamedica.pl/folia_histochemica_cytobiologica ©Polish Society for Histochemistry and Cytochemistry Folia Histochem Cytobiol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…Elevated intake of methionine and subsequent homocysteine levels have been linked to an increased risk of cardiovascular disease, primarily attributed to the induction of oxidative stress and inflammatory cascades. Methionine-induced hyperhomocysteinemia has been associated with various alterations in the structure of the aortic wall, including thickening of layers, endothelial cell hyperplasia, microthrombi formation, atheromatous plaque development, collagen accumulation, and an increase in interlamellar spaces [ 39 ]. Observational studies have also indicated a potential association between hyperhomocysteinemia and the progression of AAA [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Elevated intake of methionine and subsequent homocysteine levels have been linked to an increased risk of cardiovascular disease, primarily attributed to the induction of oxidative stress and inflammatory cascades. Methionine-induced hyperhomocysteinemia has been associated with various alterations in the structure of the aortic wall, including thickening of layers, endothelial cell hyperplasia, microthrombi formation, atheromatous plaque development, collagen accumulation, and an increase in interlamellar spaces [ 39 ]. Observational studies have also indicated a potential association between hyperhomocysteinemia and the progression of AAA [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…High levels of Hcy in the blood plasma are registered in patients with a deficiency of vitamins B6, B9, B12, excess intake of methionine. In addition, bad habits, a sedentary lifestyle and the use of certain medicines are associated with HHcy [10,11,18].…”
Section: Introductionmentioning
confidence: 99%